O que sobrou do paraíso?: o consumo e o reencantamento do mundo juvenil - Lara, Marcos Rodrigues de (2009)
This thesis has as its objective to study the urbane young people of the periphery of the city of Sao Paulo, the capacity of the consumption in enchanting the world. The study is justified by the central and growing paper that the consumption assumed along the modernity in the life of the people and more importantly for the inhabitants of the great metropolises. The point-of-view of the study was directed to the young people since they formed a social stratum of quite different characteristics from the rest as regards material and psychological frailties, since they were in the tense intermediary situation between the childhood and the maturity and since they characterized the constitution of the new generation to assume place in several fields of the social activities. The hypothesis that orientates this theory is that, since the disenchantment of the world is a psychologically unbearable condition for the man, there was a sliding of some religious significant which were accommodated in the area of the consumption, and what this would be the new field, through his elements signified once again, would be able to supply some sense for the life and for the human condition on the land in an enchanted form. Methodologically, it was selected groups of young people of the periphery of the city of Sao Paulo, of the western and of the southern zones who participated in groups discussions. The study shows in its results the capacity of the consumption in establishing elements of social aggregation, of aesthetic and erotic demonstration besides offering elements for the creation of personal and collective identities